Stability and genetic insights of the co-existence of blaCTX-M-65, blaOXA-1, and mcr-1.1 harboring conjugative IncI2 plasmid isolated from a clinical extensively-drug resistant Escherichia coli ST744 in Shanghai - Feng, Jun; Wu, Huanyu; Zhuang, Yuan; Luo, Jiayuan; Chen, Yong; Wu, Yitong; Fei, Jiayi; Shen, Qi; Yuan, Zhengan; Chen, Min (Frontiers in Public Health, 2023)
Background: Co-existence of colistin, β-lactam and carbapenem in multidrug-resistant Enterobacteriaceae isolates poses a serious threat to public health. In this study, we investigated and characterized the co-occurrence of blaCTX-M-65, blaOXA-1, and mcr-1 strain isolated from a clinical extensively-drug-resistant Escherichia coli ST744 in Shanghaiwas isolated strainsand characterized.We performed an antimicrobialAntimicrobial susceptibility test using thewas carried out by agar dilution method, conducted whole-methods. Whole genome sequencing was conducted, and analyzed the resistance genes, and sequence types of colistin in E. coli isolates. We assessed the plasmid were analyzed. Plasmid stability and amino acid mutations mutations was ere assessed in E. coli isolates.The results showed that out of 145 fecal samples collectedpECPX221 from September 2021 to January 2022, only one isolate of E. coli, named ECPX221, was isolated and found to harbor ST744 strain harbored the mcr-1 gene. Except.1 with 60,168 bp belonging to IncI2 type, except for the mcr-1.1, it also carried resistance genes for blaCTX- dfrA14, qnrS1, cmlA5, arr2, ampC, aph(4)-Ia, sul1, and aadA5.A colistin resistant E. coli ST744, named ECPX221, was identified out of 145 fecal samples collected. The strain carries a 60,168 IncI2 plasmid with the mcr-1.1 gene. The strain also has blaCTX- dfrA14, qnrS1, cmlA5, arr2, ampC, aph(4)-Ia, sul1, and aadA5 resistance genes. The plasmid pECPX221, isolated from E. coli ST744 strain harbored the mcr-1 with 60,168 bp belonging to IncI2 type,plasmid pECPX221 plasmid was capable of conjugation with an efficiency of